2001
DOI: 10.1023/a:1013090214269
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Methods of GFAP purification and obtaining of hybridoma cells producing monoclonal anti-GFAP antibodies and properties of GFAP preparation were described. The immunobloting data on specificity of obtained monoclonal antibodies are presented. A new method of GFAP immunoenzyme assay based on GFAP preparation and anti-GFAP antibodies was elaborated. Standardization of the immunoenzyme system was shown in tests for specificity, accuracy, and reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…3, c). Since cells stained with the used antibodies morphologically resembled astrocytes, we performed double immunofl uorescent staining with monoclonal antibodies to BSAT1 and polyclonal antibodies to GFAP obtained previously [3]. We found that immunofl uorescence determined by antibodies to BSAT1 and GFAP is localized in the same cells (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…3, c). Since cells stained with the used antibodies morphologically resembled astrocytes, we performed double immunofl uorescent staining with monoclonal antibodies to BSAT1 and polyclonal antibodies to GFAP obtained previously [3]. We found that immunofl uorescence determined by antibodies to BSAT1 and GFAP is localized in the same cells (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Monoclonal cells producing anti-GFAP antibodies were obtained by the standard method [8] with modifications [3]. PEG-DMSO was used as a coupling agent (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Total protein content was measured in the reaction with bicinchoninic acid [3] using BSA Protein Assay Reagent Kit 23227 (Pierce). The sample (preparation of immunoliposomes, 0.1 ml) was mixed with 2 ml working solution and incubated at 37 o C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Hybridoma producing these antibodies was created as a result of immunization of mice with preparations of cerebral capillary fractions isolated using a previously described and modified method [6]. We obtained monoclonal antibodies to glial fibrillary acidic protein (GFAP), the main marker of fibrillar astrocytes [2].…”
mentioning
confidence: 99%